Search for pentaquarks in the hadronic decays of the Z boson with the DELPHI detector at LEP - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; Anashkin, E; et al. (2007)
The quark model does not exclude states composed of more than three quarks, like pentaquark systems. Controversial evidence for such states has been published in the last years, in particular: for a strange pentaquark Θ (1540)+; for a double-strange state, the Ξ (1862)- -, subsequently called Φ (1860)- -; and for a charmed state, the Θc (3100)0. If confirmed, a full pentaquark family might exist; such pentaquark states could be produced in e+ e- annihilations near the Z energy. In this Letter a search for pentaquarks is described using the DELPHI detector at LEP, characterized by powerful particle identification sub-systems crucial in the separation of the signal from the background for these states. At 95% CL, upper limits are set on the production rates 〈 N 〉 of such particles and their charge-conjugate state per Z decay: 〈 NΘ+ 〉 × Br (Θ+ → p KS0) < 5.1 × 10-4, 〈 NΘ+ + 〉 < 1.6 × 10-3, 〈 NΦ (1860)- - 〉 × Br (Φ (1860)- - → Ξ- π-) < 2.9 × 10-4, 〈 NΘc (3100)0 〉 × Br (Θc (3100)0 → D* + over(p, ̄)) < 8.8 × 10-4. © 2007 Elsevier B.V. All rights reserved.